2008
DOI: 10.1017/s0029665108008513
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of meal and snack consumption and nutrient intake in schoolchildren in Scotland: term-time v. holidays and weekdays v. weekends

Abstract: Increasing levels of childhood obesity have raised concerns about the eating habits of children. The aim of the present study was to investigate meal and snack patterns and nutrient intakes of Scottish schoolchildren comparing term-time v. holidays and weekday v. weekends during term-time.As part of a national cross-sectional dietary survey of Scottish children conducted in 2006, a subsample of children aged 5-17 years completed a 4 d non-weighed-diet diary (n 156; eighty-one boys and seventy-five girls). Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
(1 reference statement)
0
7
0
Order By: Relevance
“…Another study indicated that American children consume a relatively high amount of energy from fat on weekends [27]. Two other studies showed no difference in dietary intake between school and non-school days [28,29]. In any case, reviews of interventions to promote physical activity [30,31] and correlates of dietary behaviour [32] in children and adolescents concluded that programmes that involve families are more likely to be effective than those that do not.…”
Section: Introductionmentioning
confidence: 99%
“…Another study indicated that American children consume a relatively high amount of energy from fat on weekends [27]. Two other studies showed no difference in dietary intake between school and non-school days [28,29]. In any case, reviews of interventions to promote physical activity [30,31] and correlates of dietary behaviour [32] in children and adolescents concluded that programmes that involve families are more likely to be effective than those that do not.…”
Section: Introductionmentioning
confidence: 99%
“…Another study indicated that American children consume a relatively high amount of energy from fat on weekends [ 27 ]. Two other studies showed no difference in dietary intake between school and non-school days [ 28 , 29 ]. In any case, reviews of interventions to promote physical activity [ 30 , 31 ] and correlates of dietary behaviour [ 32 ] in children and adolescents concluded that programmes that involve families are more likely to be effective than those that do not.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are very few published data describing and comparing intakes by day category, and where data are available they are from countries in which school meals are provided (6)(7)(8) . Texan children (9-12 years) consumed less energy and a slightly higher energy from fat on weekends (6) .…”
mentioning
confidence: 99%
“…holidays, or weekends v . weekdays ( 8 ) . However, data about foods consumed and intake of other nutrients have not been addressed in any of these studies.…”
mentioning
confidence: 99%